When MINMOD Artifactually Interprets Strong Insulin Secretion as Weak Insulin Action - Ha, Joon; Muniyappa, Ranganath; Sherman, Arthur S.; Quon, Michael J. (Frontiers in Physiology, 2021)
We address a problem with the Bergman-Cobelli Minimal Model, which has been used for 40 years to estimate SI during an intravenous glucose tolerance test (IVGTT). During the IVGTT blood glucose and insulin concentrations are measured in response to an acute intravenous glucose load. Insulin secretion is often assessed by the area under the insulin curve during the first few minutes (Acute Insulin Response, AIR). The issue addressed here is that we have found in simulated IVGTTs, representing certain contexts, Minimal Model estimates of SI are inversely related to AIR, resulting in artifactually lower SI. This may apply to Minimal Model studies reporting lower SI in Blacks than in Whites, a putative explanation for increased risk of T2D in Blacks. The hyperinsulinemic euglycemic clamp (HIEC), the reference method for assessing insulin sensitivity, by contrast generally does not show differences in insulin sensitivity between these groups. The reason for this difficulty is that glucose rises rapidly at the start of the IVGTT and reaches levels independent of SI, whereas insulin during this time is determined by AIR. The minimal model in effect interprets this combination as low insulin sensitivity even when actual insulin sensitivity is unchanged. This happens in particular when high AIR results from increased number of readily releasable insulin granules, which may occur in Blacks. We conclude that caution should be taken when comparing estimates of SI between Blacks and Whites.